FINITE ELEMENT ANALYSIS OF 3-D HELICAL GEAR DYNAMIC CONTACT CHARACTERISTICS - FU Tian; ZHAO BaiSen (Jixie qiangdu)
Load distribution characteristics of rolling bearing at high speed have important effects on the rotor system’s dynamic characteristics. In order to simulate the actual load distribution,the dynamic analysis model of rolling bearing is established by quasi-dynamic,simultaneously considering radial load,axial load,centrifugal force and gyroscopic moment acted on the rolling bearing,and study the rolling bearing load distribution under different radial load,axial load and speed conditions by MATLAB programming for solving nonlinear equations,the effect rules of contact angle and deformation are analyzed by program.